2021
DOI: 10.4103/ijo.ijo_3227_20
|View full text |Cite
|
Sign up to set email alerts
|

Fundus evaluation in COVID-19 positives with non-severe disease

Abstract: Purpose: The aim of this work was to study and document retinal changes in coronavirus disease-2019 (COVID-19) positive patients with nonsevere disease using a nonmydriatic handheld fundus camera. Methods: A cross-sectional observational study was conducted on patients affected by COVID-19 who were admitted at our center. Our study included patients with no, mild, and moderate symptoms (nonsevere cases). Intensive care unit (ICU)-admitted patients were excluded consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since none of the participants in the study or control groups had any systemic diseases, this was foreseeable. Bypareddy et al ( 10 ) also reported the lack of any fundus pathologies in non-severe COVID-19 patients, except for a single streak of retinal hemorrhage in one eye. Costa et al ( 9 ) reported the frequency of diabetic retinopathy as 52.7%.…”
Section: Discussionmentioning
confidence: 93%
“…Since none of the participants in the study or control groups had any systemic diseases, this was foreseeable. Bypareddy et al ( 10 ) also reported the lack of any fundus pathologies in non-severe COVID-19 patients, except for a single streak of retinal hemorrhage in one eye. Costa et al ( 9 ) reported the frequency of diabetic retinopathy as 52.7%.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, Lani-Louzada et al [ 41 ] studied 25 COVID-19 patients and found retinal hemorrhages in 12%. However, research by Pareddy et al [ 42 ] conducted 6 days after the onset of COVID-19 in a large cohort found nothing except one streak hemorrhage in a single patient. Moreover, retinal hemorrhages, particularly splinter hemorrhages, and tortuous retinal veins can be detected in cases of venous stasis resulting from prone positioning.…”
Section: Discussionmentioning
confidence: 99%
“…12/100 required ventilatory support. Not reported OCT, FA RVO or RAO (n = 5) Uveitis (n = 3) CSCR (n = 2) Larrea et al 96 15 (M = 9, F = 6) 49.7 ± 9 Mild (n = 14) Moderate (n = 1) 3.70 ± 0.82 months OCT, OCTA CRVO (n = 6) CRAO (n = 4) BRAO (n = 1) CWS (n = 7) Macular edema (n = 8) Macular atrophy (n = 4) Retinal ischemia (n = 10) Bypareddy et al 97 138 (M = 94, F = 44) 38.51 ± 14.4 Mild to moderate Median 6 days (range 1–9 days) Fundus photos Retinal streak hemorrhage (n = 1) Zapata et al 98 96 (M = 34, F = 35) 41.3 No symptoms (n = 24) Moderate (n = 24) Severe (n = 21) Within 3 months of confirmed COVID-19 infection. OCT, OCTA Retinal hemorrhages (n = 1) Sim et al 99 108 COVID-19+ patients 36 ± 5.4 Mild Fundus exams were performed between 12 and 20 days after PCR diagnosis.…”
Section: Methodsmentioning
confidence: 98%